Substantial improvement of geostationary satellite-derived shortwave radiation product through correcting geolocation displacement - Wangkang She; Changkun Shao; Wenjun Tang; Guopeng Zhu; Zengqiang Pang; Tongfei Liu; Shuibao Liang; Kun Yang (Remote Sensing of Environment, 2026)

Toward environmentally stable magnesium metal anodes via Bi interphase engineering for rechargeable magnesium batteries - Sitong Liang; Yuhang Chen; Xiaojin Lian; Zhimeng Tang; Lu Zhang; Xinwei She; Baihua Qu; Jingfeng Wang (Chemical Engineering Journal, 2026)

Regulating •OH generation via an S-scheme TiO2/CdZnS heterojunction for selective photocatalytic PET upcycling to glycolate - Ze Luo; Xilin She; Yifan Wu; Ning Liu; Hongwen Zhang; Jingxiang Low; Hua Tang (Chemical Engineering Journal, 2026)

Real-world exposure parameters of ten color cosmetic categories in shanghai and health risk assessment of potentially toxic elements in lipsticks - Yuanyuan She; Yang Tang; Jian Chen; Tian Chen; Wenguang Cui; Yijun Chen; Lihong Zhou; Zhu Li (Regulatory Toxicology and Pharmacology, 2026)

Metabolic rewiring and transcriptional interference underlie the biocontrol efficacy of Burkholderia arboris BB417 against Ralstonia solanacearum species complex - Shanwen Ding; Juan Zhang; Yang Wang; Guobing Lan; Lin Yu; Yafei Tang; Zhenggang Li; Bin Guo; Zifu He; Xiaoman She (Pesticide Biochemistry and Physiology, 2026)

Relationship of catalytic performance and catalyst structure evolution based on pressurized CH4-CO2 reforming reaction over carbon-supported Co-Ir alloy catalysts - Wen Tang; Jing-Pei Cao; Xiao-Yan Zhao; Dan Xie; Kai-Rui Luan; Chang-Jiang Li; Qi-Ming She; Tungalagtamir Bold (Fuel, 2026)

Harpin Protein Treatment Makes a Positive Impact on Maintaining the Postharvest Quality of Strawberry Fruits - Hao Li; Zihang Ouyang; MuSha She; ManTong Zhao; CaiXia He; Haoru Tang; Ya Luo (Journal of Plant Growth Regulation, 2026)

Associations Between Seafood Consumption and Serum PFAS Levels Among Asian/Pacific Islanders in the San Francisco Bay Area, California - Kelly Chen; Emily Beglarian; Duyen Kauffman; Ian W. Tang; Farmmary Saephan; June-Soo Park; Sabrina Smith; Key-Young Choe; Jianwen She; Nerissa Wu; Kathleen R. Attfield (Exposure and Health, 2026)

BmTrpA1-Mediated ILP/AKT/FOXO signaling Underlies Temperature-Dependent diapause in Silkworms, Bombyx mori - Yizhong Zhang; Haoping She; Shanshan Wang; Qianyi Cui; Wenjie Zhang; Shunming Tang; Xingjia Shen; Juan Zhu (Journal of Insect Physiology, 2026)

Nitrogen fertilizer mitigates warming-induced CH4 emissions in rice by regulating carbon allocation - Yingying Shen; Wenzhe Liu; Ke Liu; Wei Wu; Wentao Shi; Yufei Zhao; Chen Zhang; Yanfeng Ding; She Tang (Field Crops Research, 2026)

Automated measurement of optic nerve sheath diameter using ocular ultrasound video - Renxing Li; Weiyi Tang; Peiqi Li; Qiming Huang; Jiayuan She; Shengkai Li; Haoran Xu; Yeyun Wan; Jing Liu; Hailong Fu; Xiang Li; Jiangang Chen (Medical & Biological Engineering & Computing, 2026)

A modified PML model considering anthropogenic heat to estimate urban evapotranspiration - Xinrong Shi; Dunxian She; Jun Xia; Yongyong Zhang; Ronglin Tang; Dongdong Kong (Urban Climate, 2025)

Integrated multi-omics and network pharmacology reveals antioxidant-active metabolites and health benefits of Camellia oleifera seed oil - Lingyuan Zhou; Jiarong She; Qingyang Li; Qiong Zheng; Jie Yang; Maokai Cui; Tiantian Chen; Shiman Sun; Fubin Tang; Yihua Liu (Food Chemistry, 2025)

The mitochondrial LONP1 protease: molecular targets and role in pathophysiology - Pei Tang; Qun Zeng; Yihao Li; Jing Wang; Meihua She (Molecular Biology Reports, 2025)

Dose-dependent M2 macrophage polarization induced by Talaromyces marneffei promotes lung cancer cell growth via arginine-ornithine-cycle activation - Anqi Chen; Qian Yu; Leliang Zheng; Junqi Yi; Ziying Tang; Huabo Ge; Yue Ning; Na Yin; Yaohuan Xie; Shengnan Chen; Wenhua Shi; Xiaoling She; et al. (Medical Microbiology and Immunology, 2025)

Deciphering early molecular responses to benzotriazole ultraviolet stabilizers-induced toxicity using a dose-dependent yeast functional genomics approach - Xinyuan Xu; Linhao Zong; Shasha Zhang; Dake Cao; Ziqi Tang; Dong Chen; Ying Peng; Luhang She; Ping Jin; Xiaowei Zhang; Miao Guan (Environmental Pollution, 2025)

Nanoscale carbon quantum dots activate antiviral immune responses and modulate the heterogeneous nuclear ribonucleoprotein interface by inducing differential alternative splicing - Tahir Farooq; Muhammad Dilshad Hussain; Dandan Liu; Ali Kamran; Zifu He; Yafei Tang; Xiaoman She (Pesticide Biochemistry and Physiology, 2025)

A scaling approach for binary and grey computed tomography imaging of soil: A study in a coastal reclamation area - Xiaoqin Sun; Ana M. Tarquis; Dongli She; Xiao Han; Hongde Wang; Shengqiang Tang; Lei Gao; Pei Xin (CATENA, 2025)

Effects of structural properties of glutelin on the formation of grain quality under elevated temperatures and additional nitrogen during the grain filling period - Yufei Zhao; Wei Wu; Ke Liu; Wentao Shi; Yuxuan Peng; Chen Zhang; Yingying Shen; Wenzhe Liu; Yanfeng Ding; She Tang (Food Chemistry, 2025)

Geochemical Modelling of Fluid-Rock Interactions in Shallow Buried Carbonate Reservoirs Based on the Water Bath Instrument - Jiayi Ma; Anjiang Shen; Shuyun Xie; Min She; Huayun Tang; Emmanuel John M. Carranza; Tianfu Zhang (Journal of Earth Science, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Isotropic compression behavior of salinized unsaturated agricultural soil: An experimental and constitutive investigation - Hongde Wang; Dongli She; Jihui Ding; Shengqiang Tang; Jin Liu; Pei Xin (Soil and Tillage Research, 2025)

Regulated charge transfer by cascade dual Z-scheme heterojunction of HCdS@ZnIn2S4-Cobalt porphyrin for efficient photocatalytic solar fuel production - Tengfei Bao; Chenxi Tang; Shuming Li; Ping She; Heng Rao; Jun-sheng Qin (Chemical Engineering Journal, 2024)

Effects of warming on rice production and metabolism process associated with greenhouse gas emissions - Yingying Shen; Chen Zhang; Yuxuan Peng; Xuan Ran; Ke Liu; Wentao Shi; Wei Wu; Yufei Zhao; Wenzhe Liu; Yanfeng Ding; She Tang (Science of The Total Environment, 2024)

Effects of nitrogen application on physicochemical properties of rice starch under elevated temperature - Wenzhe Liu; Kailu Wang; Yufei Zhao; Yingying Shen; Chen Zhang; Yuxuan Peng; Xuan Ran; Hao Guo; Yanfeng Ding; She Tang (Food Chemistry, 2024)

Analysis of fluid flow characteristics in spherical nonlinear seepage flow model for dual-porous reservoir with the elastic outer boundary - Sheng Guo; Peng she Zheng; Ya Tang; Li hui Leng; Shun chu Li (Acta Geophysica, 2024)

Mitigating the adverse effect of warming on rice canopy and rhizosphere microbial community by nitrogen application: An approach to counteract future climate change for rice - Yingying Shen; Lei Xu; Hao Guo; Hashmi Ismail; Xuan Ran; Chen Zhang; Yuxuan Peng; Yufei Zhao; Wenzhe Liu; Yanfeng Ding; She Tang (Science of The Total Environment, 2023)

Se–Se bonds induced highly metallic 1T’ MoSe2.3 nanosheets cocatalysts towards boosted H2O2 photosynthesis over NH2-MIL-125 derived TiO2 nanotablets - Weikang Wang; Lele Wang; Lijuan Sun; Haopeng Jiang; Yue Liu; Qinqin Liu; Xilin She; Hua Tang (Chemical Engineering Journal, 2023)

Correction to: The Domestic Isolation of Terbinafine- and Itraconazole Resistant Trichophyton indotineae in Chinese Mainland - Xue Kong; Ge Song; Huan Mei; Hailin Zheng; Chao Tang; Sybren de Hoog; Xiaofang Li; Xiaodong She; Weida Liu; Guanzhao Liang (Mycopathologia, 2023)

Facet engineering of BiVO4 photocatalyst for the synergetic adsorption and activation of persulfate for organic pollutants degradation - Ling-Ling Zheng; Lei Tian; Dengke Wang; Ying Chen; Qian-Qian Tang; Qiu-Ju Xing; Xiao-Zhen Liu; Dai-She Wu; Jian-Ping Zou (Chemical Engineering Journal, 2023)

New record of the green algal fossil Proterocladus and coexisting microfossils from the Meso-Neoproterozoic Diaoyutai Formation in southern Liaoning, North China - Dongdong Li; Genming Luo; Qing Tang; Zhenbing She; Shuhai Xiao (Precambrian Research, 2023)

The Domestic Isolation of Terbinafine- and Itraconazole-Resistant Trichophyton indotineae in Chinese Mainland - Xue Kong; Ge Song; Huan Mei; Hailin Zheng; Chao Tang; Sybren de Hoog; Xiaofang Li; Xiaodong She; Weida Liu; Guanzhao Liang (Mycopathologia, 2023)

Three-Dimensional Ultrasonic Reverse-Time Migration Imaging of Submarine Pipeline Nondestructive Testing in Cylindrical Coordinates - Daicheng Peng; Fei Cheng; Xiaoyu She; Yunpeng Zheng; Yongjie Tang; Zhuo Fan (Journal of Marine Science and Engineering, 2023)
Submarine pipelines are a safe and energy-efficient mode of gas transport. However, due to the complex manufacturing process and harsh operating environment, submarine pipelines are subject to fatigue cracks under long-term cyclic loading. A comprehensive and high-precision characterization strategy for submarine pipelines can effectively prevent potential safety hazards and have significant economic and social repercussions. As a matter of fact, pipeline defects cannot be reliably detected with current traditional 2D methods. On the other hand, in ultrasonic testing, cylindrical geometry increases the complexity of the 3D wave field in the submarine pipeline space and significantly influences the accuracy of the detection results. In this paper, we put forward a novel method for 3D ultrasonic image testing that is suitable for cylindrical coordinates. In order to accurately simulate the ultrasonic signal received from pipelines, we generalize the 3D staggered-grid finite-difference method from Cartesian coordinates to cylindrical ones and simulate the full wave field in the 3D pipeline space. Then, signal processing is performed on the ultrasound simulation records, and 3D reverse-time migration imaging of submarine pipeline defects can be effectively achieved using the reverse-time migration method and cross-correlation imaging conditions. The results obtained from simulations and real field data show that the proposed method provides high-quality 3D imaging of defects in pipelines, taking into account multiple scattering and mode conversion information at the bottom of the defects.

Nitrogen fertilizer alleviates rice yield loss without increasing global warming potential under elevated temperatures - Yingying Shen; Kailu Wang; Yufei Zhao; Liqing Yang; Wenzhe Liu; Tongyang Yin; Xueqin Wang; Xuan Ran; Hao Guo; Yuru Ma; Xinying Wu; Yao Chen; et al. (Field Crops Research, 2023)

Lipid metabolism regulatory activity and adverse effects of fungi-derived butyrolactone I - Tanwei Gu; Weihao Chen; Jianglian She; Bin Yang; Lan Tang; Huaming Tao; Jingxia Huang; Xuefeng Zhou (Natural Product Research, 2023)

Hot-topics cross-propagation and opinion-transfer dynamics in the Chinese Sina-microblog social media: A modeling study - Fulian Yin; Yuwei She; Yanyan Pan; Xinyi Tang; Haotong Hou; Jianhong Wu (Journal of Theoretical Biology, 2023)

Nitrogen Alleviated the Deterioration of Rice Quality by Affecting the Accumulation of Grain Storage Protein Under Elevated Temperature - Yufei Zhao; Xuan Ran; Tongyang Yin; Hao Guo; Xiaoyang Zhang; Yingying Shen; Wenzhe Liu; Yanfeng Ding; She Tang (Journal of Plant Growth Regulation, 2023)

Identification and genomic characterization of Ralstonia pseudosolanacearum strains isolated from pepino melon in China - Shanwen Ding; Lin Yu; Guobing Lan; Yafei Tang; Zhenggang Li; Zifu He; Xiaoman She (Physiological and Molecular Plant Pathology, 2023)

Can the Leading Officials’ Accountability Audit of Natural Resources policy stimulate Chinese heavy-polluting enterprises’ green behavior? - Yunqiang Liu; Yanan She; Sha Liu; Hong Tang (Environmental Science and Pollution Research, 2022)

Combining polyacrylamide amendment to mitigate negative effect of biochar on the soil conservation of saline-sodic soil - Shengqiang Tang; Dongli She; Hongde Wang (Arabian Journal of Geosciences, 2021)

Complete genome sequence of a previously undescribed monopartite begomovirus and betasatellite infecting Malvastrum coromandelianum in Cambodia - Yafei Tang; Zhenggang Li; Xiaoman She; Lin Yu; Guobing Lan; Lihua Lv; Judith K. Brown; Zifu He (Archives of Virology, 2021)

Spatial distribution of the oxygen-18 in precipitation in China based on a new empirical model - Pei Zhao; Zheng-sheng Guo; Dong-li She; Xiang-yu Tang (Journal of Mountain Science, 2019)

Comparative genomics for non-O1/O139 Vibrio cholerae isolates recovered from the Yangtze River Estuary versus V. cholerae representative isolates from serogroup O1 - Li Gong; Pan Yu; Huajun Zheng; Wenyi Gu; Wei He; Yadong Tang; Yaping Wang; Yue Dong; Xu Peng; Qunxin She; Lu Xie; Lanming Chen (Molecular Genetics and Genomics, 2019)

Fertility outcomes in infertile women with complex hyperplasia or complex atypical hyperplasia who received progestin therapy and in vitro fertilization - Miao Li; Jia-lun Song; Ying Zhao; She-ling Wu; Hong-bin Liu; Rong Tang; Lei Yan (Journal of Zhejiang University-SCIENCE B, 2017)

Nitrogen fertilizer application affects lodging resistance by altering secondary cell wall synthesis in japonica rice (Oryza sativa) - Wujun Zhang; Longmei Wu; Yanfeng Ding; Xiong Yao; Xiaoran Wu; Fei Weng; Ganghua Li; Zhenghui Liu; She Tang; Chengqiang Ding; Shaohua Wang (Journal of Plant Research, 2017)

Molecular characterization of a novel bipartite begomovirus isolated from Lycianthes biflora in China - Y. F. Tang; Z. F. He; J. K. Brown; X. M. She; G. B. Lan (Archives of Virology, 2017)

Traditional symbiotic farming technology in China promotes the sustainability of a flooded rice production system - Huabin Zheng; Huang Huang; Can Chen; Zhiqiang Fu; Huaqin Xu; Shuduan Tan; Wei She; Xiaolan Liao; Jianwu Tang (Sustainability Science, 2017)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Spatial distribution and temporal trends of mercury and arsenic in remote timberline coniferous forests, eastern of the Tibet Plateau, China - Ronggui Tang; Haiming Wang; Ji Luo; Shouqin Sun; Yiwen Gong; Jia She; Youchao Chen; Yang Dandan; Jun Zhou (Environmental Science and Pollution Research, 2015)

A Proteomic Approach to Analyze Differential Regulation of Proteins During Bud Outgrowth Under Apical Dominance Based on the Auxin Transport Canalization Model in Rice (Oryza sativa L.) - Junxu Xu; Chengqiang Ding; Yanfeng Ding; She Tang; Manrong Zha; Baojie Luo; Shaohua Wang (Journal of Plant Growth Regulation, 2015)

The evaluation of the association constant between R-SN and Hg2+ - Jian-she Tang; Li Xiang; Hai-zhou FAN (Environmental Monitoring and Assessment, 2014)

Identification and molecular characterization of two begomoviruses from Pouzolzia zeylanica (L.) Benn. exhibiting yellow mosaic symptoms in adjacent regions of China and Vietnam - Y. F. Tang; Z. G. Du; Z. F. He; Judith K. Brown; X. M. She (Archives of Virology, 2014)

Overexpression of a dominant-negative mutant of SIRT1 in mouse heart causes cardiomyocyte apoptosis and early-onset heart failure - WenLi Mu; QingJun Zhang; XiaoQiang Tang; WenYan Fu; Wei Zheng; YunBiao Lu; HongLiang Li; YuSheng Wei; Li Li; ZhiGang She; HouZao Chen; DePei Liu (Science China Life Sciences, 2014)

Heavy metal concentrations in timberline trees of eastern Tibetan Plateau - Ji Luo; Jia She; Peijun Yang; Shouqin Sun; Wei Li; Yiwen Gong; Ronggui Tang (Ecotoxicology, 2014)

Identification and molecular characterization of a single-stranded circular DNA virus with similarities to Sclerotinia sclerotiorum hypovirulence-associated DNA virus 1 - Zhenguo Du; Yafei Tang; Songbai Zhang; Xiaoman She; Guobing Lan; Arvind Varsani; Zifu He (Archives of Virology, 2014)

Molecular characterization of a novel monopartite begomovirus isolated from Pouzolzia zeylanica in China - Y. F. Tang; Z. G. Du; Z. F. He; X. M. She; J. H. Cai (Archives of Virology, 2013)

The influence of water content on soil erosion in the desertification area of Guizhou, China - Jie Zhou; Yi-qun Tang; Xiao-hui Zhang; Tian-yu She; Ping Yang; Jian-xiu Wang (Carbonates and Evaporites, 2012)

Vascular endothelial growth factor-C promotes the growth and invasion of gallbladder cancer via an autocrine mechanism - Yanling Chen; Lei Jiang; Feifei She; Nanhong Tang; Xiaoqian Wang; Xiujin Li; Shenghua Han; Jinhai Zhu (Molecular and Cellular Biochemistry, 2010)

Monosialoanglioside (GM1) prevents lead-induced neurotoxicity on long-term potentiation, SOD activity, MDA levels, and intracellular calcium levels of hippocampus in rats - Jia-Qi She; Ming Wang; Da-Miao Zhu; Mingliang Tang; Ju-Tao Chen; Lang Wang; Di-Yun Ruan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)